Analisis Kelengkapan Pengisian Berkas Rekam Medis - Fahrunisa Fahrunisa; Musparlin Halid; Ikhwan Ikhwan (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Minimum Service Standards (MSS) indicators in the form of completing the filling of medical record documents for 24 hours. There are medical record files and informed consent that are incomplete and not in accordance with MSS. The purpose of the study was to identify and analyze the completeness of the medical record file. The study was conducted at the Hospital of NTB Province. The purpose of the study was to determine the level of completeness of the contents of the medical record document. This research uses quantitative type. The sample is 87 medical record files. Services in the medical record section are not in accordance with the MSS. With details of the completeness of the contents of the medical record document for 24 hours after the service, it has not been completely filled out, such as the initials of the doctor/nurse (62%). Indicators of filling out informed consent from completeness after the patient is given incomplete information, such as providing information (76%), type of information (76%), doctor's signature (76%), and signatures of witnesses 1 and 2 (76%). The medical record document has not been filled in completely by the medical record officer.